Chronic Carpometacarpal Dislocation of the Thumb: A Case Report and Review of the Literature. Issue 3 (July 2018) - McCarley, Matthew; Foreman, Mark
Abstract : Case: We report a case of a chronic, irreducible carpometacarpal (CMC) dislocation of the thumb, which was managed with a trapeziometacarpal arthrodesis. Conclusion: This case demonstrates that arthrodesis is a suitable salvage procedure for chronic, irreducible CMC dislocations of the thumb.